2015
DOI: 10.1155/2015/482839
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Metastasis from Breast Cancer in a Male Patient with HIV

Abstract: Context. Breast cancer (BC) in men is a rare condition, corresponding to 1% of all neoplasms in this gender. Some studies show that up to 93% of BC cases in men are advanced disease. If its occurrence constitutes an uncommon fact, the appearance of a metastasis to the central nervous system (CNS) is extremely rare. The objective of the present study is to present the case of a male patient, bearer of HIV infection, who presented with BC and later metastasis to the CNS. We also include a brief review of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It has been reported that about 93% of the male breast cancers were diagnosed at an advanced stage, in which 30% were diagnosed with metastasis as the first presentation. 1 This was probably because of a lack of awareness among men leading to the delay in seeking treatment. The reported common sites of metastasis in male breast cancer are bones (48.78%), lungs (29.26%), liver (17.07%), spine (30%) skin and pleura.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that about 93% of the male breast cancers were diagnosed at an advanced stage, in which 30% were diagnosed with metastasis as the first presentation. 1 This was probably because of a lack of awareness among men leading to the delay in seeking treatment. The reported common sites of metastasis in male breast cancer are bones (48.78%), lungs (29.26%), liver (17.07%), spine (30%) skin and pleura.…”
Section: Discussionmentioning
confidence: 99%
“…Male breast cancer is rare and accounts for 1% of all malignant breast neoplasm cases. 1,2 Male breast cancer has many differences from female breast cancer in terms of age of diagnosis, frequency of histological subtype and hormonal receptor expression frequency. 3 Male breast cancer has a peak incidence at the age of 71 years in comparison to female breast cancer, which shows bimodal age frequency distribution with a peak incidence at the age of 52 and 72 years respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, a very few papers are dedicated to the thirst feeling in breast cancer, and all of them are focused on the issue during BC treatment and BC patients specifically with diabetic history. On the other side, it is well known that reduced water intake leading to mild or severe body dehydration is a strong risk factor for several pathologies including breast malignancies [18] and headache/migraine attacks [19]. However, if any, highly restricted information is available regarding potential mechanisms of the dehydration in breast cancer predisposition and pathology.…”
Section: Thirst Feeling and Dehydration In Bcmentioning
confidence: 99%